The Gap in Health Status Between Manitoba First Nations and All Other Manitobans Is Widening - Alan Katz; Kathi Avery Kinew; Leona Star; Carole Taylor; Ina Koseva (International Journal of Population Data Science, 2020)
Introduction A 2002 report described the gap in health status between First Nations (FN) and all other Manitobans (AOM). That report was widely quoted in the context of other initiatives recognizing the inequities in Canadian society.